Prevalensi dan insidensi ektoparasit pada udang vaname (Litopenaeus vannamei) di tambak CV. Pasifik Delyano Farm - Mokoginta, Leyda H.; Kreckhoff, Reni L.; Tumbol, Reiny A.; Longdong, Sammy N.J.; Sambali, Hariyani; Mingkid, Winda M. (e-Journal BUDIDAYA PERAIRAN, 2023)
This study aimed to inventory the parasites that attack vaname shrimp (Litopenaeus vannamei) and to determine and determine the prevalence and incidence rates of parasites that infect vaname shrimp. The research was carried out at CV. Pasifik Delyano Farm, Iyok Village, District. Bolangitang, Kab. North Mongondow. Parasite identification is carried out in the Laboratory of Aquaculture Technology FPIK Unsrat. The test animals used in this rstudy were vannamei shrimp with a weight ranging from 7-10 grams with a length of 10-15 cm. The number of shrimp samples taken was 10 in the pond. Methods for examining and observing ectoparasites were carried out on the gills, walking legs, swimming legs, and tail of vannamei shrimp and then identified to obtain prevalence and incidence rates. The observation results were then analyzed using prevalence and incidence rate formulas. Based on the research results, two types of parasites were found that infect shrimp, walking legs, swimming legs, and tail, namely Vorticella and Zootanium. Prevalence rates based on parasite type were obtained in Vorticella sp. 40% and Zoothamnium sp 30% in the category of infections that generally occur while the prevalence rate based on organs, swimming legs was higher (0.4%) than in tail (0.3%) and walking legs (0.2%). based on the level of parasite incidence in all observed shrimp organs, Zoothamnium sp. was higher than Vorticella sp.  Keywords: diseases, parasites, aquaculture, intensive cultivation